Regional Development and Income Distribution The Case of Greece - Katerina Dimaki; Vasilis Angelis; Eleni Gaki (European Regional Science Association (ERSA), 2010)
The distribution of income has always been a main concern of economic theory and policy. Classical economists were concerned with the distribution of income between the main factors of production, land, labour and capital. Modern economists, on the other hand, are concerned with the distribution of income across individuals and households. Furthermore, the unequal distribution of personal income and wealth is one of the most prominent features of our society and one which has a profound effect on economic and social relationships. The theoretical aspects of income distribution and a number of income inequality measures have been presented in some previous work (Dimaki et al. 2001). In this paper we focus on income inequality at a regional level. Almost all countries face regional disparities, due to a variety of reasons, historic, socioeconomic, structural and geographic, leading to a number of adverse consequences for the less favored regions. Hence, Governments take certain alternative measures to alleviate those disparities and assist the less developed regions. Our objective in this paper is to: - Define a measure expressing a region's current state of development and future prospects. - Assess the changes in that measure over time, resulting from both endogenous development and the implementation of alternative state measures for its improvement. - Relate the changes in that measure to the respective changes in the regional income inequality measures over the same period of time. The theoretical findings will be applied to the case of Greek regions over a period of time and the results will be presented and critically discussed.
Keywords: 330; Income Distribution; Income Inequality; Regional Development